Are Stress-Related Hormones Involved in the Temperature-Dependent Sex Determination of the Broad-Snouted Caiman? - Iungman, Josefina Luciana (2015)
In some reptiles, gonadal outcome is regulated by temperature during a critical period of the embryonic development. Gonadal steroid hormones are seen as effectors of the gonadal differentiation process. Recently, stress and glucocorticoids (GCs), stress-related hormones in vertebrates, have been considered as potential modulators of the sex determination process in some vertebrates that present temperature-dependent sex determination (TSD). In reptiles, corticosterone is the main GC produced, and its administration to eggs causes a bias in sex ratio in some lizards. In this context, we aim at assessing whether dexamethasone (Dex), a potent synthetic glucocorticoid, can modify the sex ratio in Caiman latirostris, a species with strong TSD. As a first step, we incubated embryos at masculinizing temperatures (33°C; 100% males). Different doses of Dex were topically applied to the eggshell at stage 20, prior to gonadal differentiation. We assessed embryonic development at stages 22 and 25 and evaluated some physiological and morphological hatchling traits. Embryonic mortality was not affected by dexamethasone manipulation. No effects of Dex on sex ratio were found and all animals analyzed histologically possessed testes. However, older embryos and hatchlings from Dex treated eggs were heavier, larger, and hatched earlier than control individuals. Our results do not account for Dex involvement in the process of ovarian differentiation, at least under a strong masculinizing temperature. Nevertheless, they suggest that Dex might accelerate embryo development by enhancing intermediate metabolism and/or by stimulating growth hormone secretion.